Exploited Fishery Resources of Muvattupuzha River, Kerala, India - Renjithkumar, C. R.; Roshni, K.; Kurup, B. Madhusoodana (Fishery Technology, 2025)
The exploited fishery resources of Muvattupuzha river have been estimated as 45.01 t during 2009-10. Twenty three fish species belonging to 6 orders and 20 genera contributed to the fishery of this river. Highest landings was recorded during post-monsoon season (21.87 t) followed by pre-monsoon season (15.77 t) and lowest in monsoon (7.38 t). Family Cyprinidae ranked first among fish groups with a numerical strength of 6 species. The landings were represented by two endangered (Hypselobarbus curmuca and Tor khudree) and one vulnerable (Horabagrus brachysoma) fish species. Gibelion catla was the only non-native species represented in the landings and Clarias gariepinus were the non-native species represented in the landings. Wallago attu (7.62 t), Labeo dussumieri (7.21 t), H. curmuca (4.90 t), Channa striatus (4.6 t) and H. brachysoma (3.67 t) were the dominant fishes in the landings. Among the landing centres, Mulakulam accounted for 32% to the total fish landings, followed by Kalampoor (27%). Gillnets (88%) contributed the major bulk of the fish landings followed by seine nets (11%). Catch per unit effort recorded in gillnet for major species were W. attu (0.11 kg h-1), Channa striata (0.08 kg h- 1), T. khudree (0.08 kg h-1), G. catla (0.08 kg h-1) and C. marulius (0.07 kg h-1). In seines, highest catch per unit effort was recorded for C. striata (0.28 kg h-1) followed by C. marulius (0.20 kg h-1) and H. brachysoma (0.08 kg h-1).